2020
DOI: 10.1021/acsomega.0c03004
|View full text |Cite
|
Sign up to set email alerts
|

Model-Informed Drug Discovery and Development in Pulmonary Delivery: Biopharmaceutical Pharmacometric Modeling for Formulation Evaluation of Pulmonary Suspensions

Abstract: For respiratory conditions, targeted drug delivery to the lungs could produce higher local concentrations with reduced risk of adverse events compared to systemic administration. Despite the increasing interest in pulmonary delivery, the pharmacokinetics (PK) of drugs following pulmonary administration remains to be elucidated. In this context, the application of modeling and simulation methodologies to characterize PK properties of compounds following pulmonary administration remains a scarcity. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 41 publications
(74 reference statements)
0
6
0
Order By: Relevance
“…Simulations of lipid bilayers containing products of lipid oxidations have found a decrease in permeability for the case of oxysterols [550] and tail oxidized phosphatidylcholine [481]. From the standpoint of pharmaceutical research, the most interesting are studies of membranes that form a boundary with an extracellular environment, including bacterial membranes [415,[610][611][612][613][614][615][616], the stratum corneum, i.e., the most external layer of the skin [617][618][619][620][621][622][623][624][625][626], membranes present in the eyes [557,[627][628][629][630][631], and the ocular mucous membrane [632], or lung surfactant monolayers [263,558,[633][634][635][636][637][638]. Specifically, MD simulations have been used in studies of enhancer effects on the permeability of the stratum corneum (e.g., [544]).…”
Section: Translocation Through the Membranementioning
confidence: 99%
“…Simulations of lipid bilayers containing products of lipid oxidations have found a decrease in permeability for the case of oxysterols [550] and tail oxidized phosphatidylcholine [481]. From the standpoint of pharmaceutical research, the most interesting are studies of membranes that form a boundary with an extracellular environment, including bacterial membranes [415,[610][611][612][613][614][615][616], the stratum corneum, i.e., the most external layer of the skin [617][618][619][620][621][622][623][624][625][626], membranes present in the eyes [557,[627][628][629][630][631], and the ocular mucous membrane [632], or lung surfactant monolayers [263,558,[633][634][635][636][637][638]. Specifically, MD simulations have been used in studies of enhancer effects on the permeability of the stratum corneum (e.g., [544]).…”
Section: Translocation Through the Membranementioning
confidence: 99%
“…The hepatic stability of 6f was investigated in our previous report; 42 6f performed inadequately in hepatic stability testing when exposed to human and rat microsomes where the 6f half-life was determined to be relatively short. These results were further corroborated in a PK profiling study of 6f following intratracheal administration in rats as a coarse suspension.…”
Section: Discussionmentioning
confidence: 99%
“…More extensively, the application of biopharmaceutical pharmacometrics (BPMX)-i.e., pharmacometric modeling incorporating biopharmaceutical principles has been demonstrated as a valuable tool in drug discovery and development. For instance, Sou et al [59] reported the application of BPMX for the PK analysis of three investigational antimicrobial agents following pulmonary administration of different suspension formulations. They developed a PK model considering formulation properties and provided a mechanism to estimate dissolved drug concentrations in the lungs.…”
Section: Pk/pd Analysis In Drug Developmentmentioning
confidence: 99%